The influence of entrepreneurial capital on social transformation by social enterprises in Kiambu County, Kenya (International Journal of Scientific Research and Management (IJSRM), 2021)
Several studies have found entrepreneurial capital or finance to be significant in growth and performance of enterprises. This development has led the researchers in the present study to investigate the role of entrepreneurial capital in social transformation by social enterprises in Kiambu County, Kenya. This journal examines the influence of entrepreneurial capital on social transformation. The context of the study was Kiambu County, Kenya. Social entrepreneurship theory, market failure theory, empowerment theory, planned behavior theory and cultural dimension’s theory guided the study. The study used a descriptive survey design guided by a mixed methods research approach. The sample size was 322 social enterprises drawn from a target population of 1944 social enterprises distributed all from Kiambu County. Data was collected using survey questionnaires and interview guide instruments. Simple random sampling technique was used to get the proportionate sample for each strata. Data was descriptively and inferentially presented and analyzed. The findings shows R-value of .614, R2 value of .377, adjusted R2-value of .375; F-statistics value is 1977.052 greater than critical value of 3.85 and p- value was 0.000. The study concludes that entrepreneurial capital has a statistically significant and positive effect on social transformation by social enterprises.